PREVALENCE AND ANTIBIOTIC SUSCEPTIBILITY OF ACINETOBACTERIN A TERTIARY CARE HOSPITAL IN CHENNAI, INDIA - A., ANGELINE ANJALI; V. K., ABIRAMASUNDARI (International Journal of Current Pharmaceutical Research, 2021)
Objective: The present study is to determine the prevalence and antibiotic susceptibility of Acinetobacter species in samples collected from patients in tertiary care hospital in Chennai. Methods: A total of17,827patient’s clinical samples were collected from various wards and ICUs of Saveetha Medical College and Hospital, Chennai, Tamilnadu over a period of 7 mo [between January 2020 and July 2020]. All samples were tested in the microbiology lab of Saveetha Medical College and Hospital using standard operating procedures. Results: Out of 17,827 samples, 2,816 were culture positive. 122 of the isolates tested positive for Acinetobacter spp.and 81.1% of the isolates belonged to Acinetobacterbaumannii. Most of the infection occurred in the age group of 21-40 y and predominantly in female patients (female, male ratio 1.9:1).General wards contributed to 54.9% of the Acinetobacter infection, followed by ICU(27%) and OPD(18%). Maximum isolates were recovered from urine(34.4%) and endotracheal secretions(29.5%).60.7% of the Acinetobacterspp were multidrug-resistant(MDR)i.e. resistant to more than 3 antibiotic group.In our study, most Acinetobactersppwere resistant to penicillin(46-100%), third and fourth generation cephalosporin (36-61.5%), carbapenems (34.4-82.8%)and quinolones(39.3-46.7%). None of the isolates were resistant to colistin. 93.4% ofisolates were sensitive to tigecycline and 87.7% sensitive to amikacin. Conclusion: Our study observed a high incidence of MDR inAcinetobacterspp, which is in line with most of the research findings in recent times. Most of Acinetobacterspp were resistant to penicillin, third and fourth generation cephalosporins, quinolones, carbapenems,which is alarming as it leaves fewer options for the line of treatment. Some strains were sensitive to cefepime, ceftazidime, piperacillin-tazobactam, levofloxacin, imipenem and meropenem. Considering the increasing MDR nature of Acinetobacterspp a combination of the former along with colistin, tigecycline, amikacin(which have shown more than 85% sensitivity) would need to be studied.Also, strict measures to control the spread of Acinetobacter infection, better management of antibiotics usage and newer therapeutic option for treatment need to be looked at.